Rancang Bangun Game Edukasi Math Whizzer Untuk Siswa UPTD SDN 08 Pemali - Anjelia, Nisvina; Azzahra Rahmanda, Iffah; Andriyanto, Sidhiq; Setya Pratama, Muhammad (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Mathematics learning is often considered difficult by elementary school students, which has an impact on their low interest and learning achievement. To overcome this problem, an Android-based educational game called